2017
DOI: 10.1080/03601234.2017.1301755
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS determination of pesticide residues in fruits and vegetables

Abstract: The aim of the research is to evaluate pesticide residue contamination of fresh and frozen fruits and vegetables, agricultural raw material, purchased from Polish farmers for production of frozen fruits and vegetables, and the estimation of the multiresidue method effectiveness expressed as the proportion of pesticides detected in food samples to the total number of pesticides analyzed by multiresidue methods. A total of 144 samples (of black currants, red currants, raspberries, cherries, strawberries, blackbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…leading to acute, chronic, or subchronic problems [7]. Some fruit and vegetables are at the top of the list of foods that contain the highest pesticide levels, since most of them are grown close to the soil, are eaten raw, and are without the need to remove the skin [8]. Lettuce is one of the most consumed leafy vegetables worldwide, being a basic component of raw salads prepared in domestic households.…”
Section: Introductionmentioning
confidence: 99%
“…leading to acute, chronic, or subchronic problems [7]. Some fruit and vegetables are at the top of the list of foods that contain the highest pesticide levels, since most of them are grown close to the soil, are eaten raw, and are without the need to remove the skin [8]. Lettuce is one of the most consumed leafy vegetables worldwide, being a basic component of raw salads prepared in domestic households.…”
Section: Introductionmentioning
confidence: 99%
“…The main routes of exposure to CBZ include inhalation and consumption of contaminated water, fruits, and vegetables. 7 Several experimental studies have demonstrated that CBZ adversely affects the reproductive system and disrupts endocrine function in animals. 8,9 Recent studies have also shown that CBZ induces renal and hepatic toxicity 10,11 which can be associated with gut microbiota dysbiosis and hepatic lipid metabolism disorder.…”
Section: Introductionmentioning
confidence: 99%
“…They are also rich in organic acids (citric, fumaric, tartaric) that determine taste and flavor and typically contain low amounts of fat and proteins (Ruby et al 2000;Sturm et al 2003). Some fruits (mainly berries) are rich sources of flavonoids and other phenolic compounds possessing antioxidant activity (Määttä et al 2003;Pavlović et al 2013), but fruits might be also a source of toxic elements, mycotoxins, or pesticides (Pavlović et al 2013;Stachniuk et al 2017).…”
Section: Preparation Of Fruits and Their Related Products For Patulinmentioning
confidence: 99%